Geochemistry of storing CO2 and NOx in the deep Precipice Sandstone - Pearce, J. K.; Altaf, I.; Kirste, D.; Golding, S. D.; Dawson, G. K. W.; Undershultz, J. (ASEG Extended Abstracts, 2018)
The Precipice Sandstone in the Surat Basin is being appraised for CO2 geological storage owing to its high porosity and permeability and expected high injectivity. Generally it is quartz rich with variable kaolinite, however detailed characterisation of core shows that it contains minor to trace amounts of potentially reactive minerals including carbonates, plagioclase, chlorite, and muscovite, increasing towards the overlying Evergreen Formation top seal. The Evergreen Formation is more variable, with interbedded low porosity and permeability mudstones, fine-grained sandstones, and calcite cemented zones. Injected CO2 dissolves into formation water forming carbonic acid. The geochemical reactivity of drill core samples affects the predicted pH and the dissolution or precipitation of minerals which could permanently trap CO2 as carbonates such as siderite, or dynamically change porosity and permeability altering CO2 migration. Comparative kinetic geochemical modelling of the CO2 reactivity of four representative mineralogies from drill core samples from deeper parts of the central basin indicates that the Evergreen Formation is potentially more reactive to CO2 than the Precipice Sandstone, especially for calcite or siderite containing zones. In the Precipice Sandstone small amounts of albite and siderite dissolved with traces of siderite and kaolinite precipitated. Dissolution of calcite and siderite in the Evergreen Formation favourably buffered acidity, with predicted precipitated minerals including siderite, kaolinite, ankerite, and smectites. The geochemical models indicate overall changes to porosity are however minor. Recent data from capture technologies has reported that CO2 from coal combustion may retain NOx impurities in the form of NO. Simulations with the addition of 30-100 ppm NO in the CO2 stream indicated the generated pH in the quartz rich Precipice Sandstone is similar to that on injection of pure CO2 after 30 years. The precipitation of Fe-rich smectite clays was additionally predicted.